2020
DOI: 10.3389/fgene.2020.538600
|View full text |Cite
|
Sign up to set email alerts
|

Genomic Heritability and Genome-Wide Association Studies of Plasma Metabolites in Crossbred Beef Cattle

Abstract: Blood Metabolites in Crossbred Cattle candidate genes were identified based on additive genetic variance explained by SNP windows of 10 consecutive SNPs. The observed heritability estimates and the candidate genes and networks identified in this study will serve as baseline information for research into the utilization of plasma metabolites for genetic improvement of crossbred beef cattle.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 59 publications
0
14
0
Order By: Relevance
“…Our results showed that 31 metabolites had low to moderate heritability and two metabolites had relatively high heritability (> 0.4). In a study of beef cattle, only 11 of 33 metabolites measured (29 in common with this study) were reported to be heritable 17 . Similar heritability estimates to Li et al 17 were reported here for betaine, creatinine, pyruvic acid and citric acid.…”
Section: Metabolitementioning
confidence: 50%
See 1 more Smart Citation
“…Our results showed that 31 metabolites had low to moderate heritability and two metabolites had relatively high heritability (> 0.4). In a study of beef cattle, only 11 of 33 metabolites measured (29 in common with this study) were reported to be heritable 17 . Similar heritability estimates to Li et al 17 were reported here for betaine, creatinine, pyruvic acid and citric acid.…”
Section: Metabolitementioning
confidence: 50%
“…In a study of beef cattle, only 11 of 33 metabolites measured (29 in common with this study) were reported to be heritable 17 . Similar heritability estimates to Li et al 17 were reported here for betaine, creatinine, pyruvic acid and citric acid. In our study, other metabolites, such as ketone bodies (3-hydroxybutyric acid, acetoacetate and acetone), creatine, succinate, formate, and methylhistidine, showed negligible heritability estimates, suggesting that they are primarily influenced and manipulated by environmental effects such as diet, and/or age, health status etc.…”
Section: Metabolitementioning
confidence: 50%
“…The population of animals was obtained from the Phenomic Gap Project that aimed to generate phenotypes of feed efficiency, carcass and meat quality as well as genomic data for Canadian crossbred beef animals [ 38 ]. Details of animal management, the herd, and animal breeds were previously described [ 12 , 39 41 ]. In summary, the population used in this study consisted of 493 crossbred bulls ( n = 93), heifers ( n = 125) and steers ( n = 275) that were born between 2002 and 2011.…”
Section: Methodsmentioning
confidence: 99%
“…These blood samples were used to quantify metabolites using nuclear magnetic resonance (NMR) spectroscopy. The procedure of metabolite quantification using NMR was previously described by Li et al [ 39 ]. Thirty-one metabolites and their concentration levels (µM) were quantified from plasma.…”
Section: Methodsmentioning
confidence: 99%
“…Metabolomics is the joint to connect genotypes with phenotypes [6], so their relationships are currently interpreted by the metabolome genome-wide association study (mG-WAS) using metabolites as the metabolic phenotypes. The integrated genomic−metabolomic analysis is considered as a critical supplement to biology and physiology, as the metabolites provide the details of physiological state that can drive genetic variant-associated metabolites to display larger effect sizes, and then the quantitative trait loci (QTLs) affecting metabolite concentrations can be identified [53, [59][60][61][62][63].…”
Section: Genomics-metabolomic Analysismentioning
confidence: 99%